The effects of platelet activating factor and retinoic acid on the expression of ELAM-1 and ICAM-1 and the functions of neutrophils - Si-Feng Chen (Mediators of Inflammation)
Preincubation of pulmonary microvascular endothelial cells (PMVECs) with platelet-activating factor (PAF) for 3.5 h increased the adhesion rate of polymorphonuclear leukocytes (PMNs) to PMVECs from 57.3% to 72.8% (p < 0.01). Preincubation of PMNs with PAF also increased PMN-PMVEC adhesion rate. All-trans retinoic acid (RA) blocked the adherence of untreated PMNs to PAF-pretreated PMVECs but not the adherence of PAF-pretreated PMNs to untreated PMVECs. PAF increased the expression of intercellular adhesion molecule-1 (ICAM-1) and E-selection (ELAM-1) on PMVECs, PMN chemotaxis to zymosan-activated serum and histamine, and PMN aggregation and the release of acid phosphatase from PMNs. Co-incubation of RA inhibited PAF-induced PMN aggregation, the release of acid phosphatase from PMNs, and PMN chemotaxis to zymosan-activated serum and histamine while the expression of ICAM-1 and ELAM-1 did not change. Our results suggest that RA can be used to ameliorate PMN-mediated inflammation.